Egg consumption and risk of type 2 diabetes mellitus in middle and elderly Chinese population: An observational study. Issue 16 (April 2020) - Ni, Li-Ping; Du, Li-Yun; Huang, Yi-Qian; Zhou, Jian-Ying
Abstract : Abstract: Data on the association between egg consumption and the risk of type 2 diabetes mellitus (T2DM) in the Chinese population are scarce. In the present study, we aimed to examine the association between egg consumption and the risk of T2DM in a middle and elderly Chinese population. A total of 3298 subjects (1645 men and 1653 women) from the Nutrition and Health Survey (2015–2017) in Hangzhou city were selected for the final analysis. Egg consumption was assessed using a validated food frequency questionnaire. All biochemical data and anthropometric measurements were collected following standardized procedures. Multivariable logistic regression analyses were used to assess the association between egg consumption and the risk of T2DM and the results were presented as odds ratios and 95% confidence interval (CI). Restricted cubic spline combined with logistic regression was used to explore the dose-response relationship between egg consumption and T2DM. Among 3298 subjects, 693 (21.0%) people had T2DM. Compared with participants who did not consume egg per week, the multivariable-adjusted odds ratios were 0.97 (95%CI : 0.78–1.21), 1.08 (95%CI : 0.91–1.06), 1.20 (95%CI : 0.94–1.55), 1.27 (95%CI : 0.99–1.68) in men ( P  > .05); 1.06 (95%CI : 0.81–1.37), 0.97 (95%CI : 0.78–1.21), 1.26 (95%CI : 0.99–1.59), 1.19 (0.92–1.54) in women ( P  > .05); 0.89 (95%CI : 0.79–1.04), 0.98 (95%CI : 0.91–1.06), 1.06 (95%CI : 0.87–1.30), 1.09 (95%CI : 0.88–1.34) in both men and women for egg consumption 0∼7, 7, 7∼14, and ≥14 eggs/week, respectively ( P  > .05). The dose-response curve showed that, with the increase of egg consumption, the risk of T2DM first increased and then decreased ( P  = .027). We found that the association between egg consumption and T2DM was nonlinear, and higher egg consumption was not associated with an elevated risk for T2DM in middle-aged and elderly Chinese. However, future prospective studies are needed to confirm these findings.